Cardiovascular risk in primary care: comparison between Framingham Score and waist circumference - Nina Vitória de Souza Silva Andrade; Isis Marinho de Noronha; Larisse Xavier Almeida; Fernanda Siqueira; Tatiana Onofre (Hospital de Clínicas de Itajubá, 2021)
Objectives: To estimate and compare the cardiovascular risk using the Framingham risk score (FRS) and waist circumference (WC) in primary care individuals and, secondarily, determine the main factors associated with these scores. Methods: Cross-sectional study involving individuals of both sexes attended in a primary health unit and aging between 30 and 74 years. The cardiovascular risks (FRS and WC) were stratified as low, intermediate, and high. The weighted Kappa coefficient was used to assess agreements between scores. Results: Fifty-five individuals (52.8 ± 9.4 years, 70.9% women) were evaluated. Using the FRS, 40.0% of the sample presented a low risk, 45.5% intermediate risk, and 14.5% high risk of cardiovascular disease. Conversely, when analyzed using the WC score, the highest frequency (71%) was observed in the high-risk category. Also, no agreement (K= 0.36; p= 0.55) was found between scores. FRS was associated with hypertension (p<0.01), diabetes (p=0.01), and stress in women (p=0.01), while the WC score was associated with hypertension (p=0.02), obesity (p<0.01), and high-density lipoprotein cholesterol HDL-c (p=0.03). Conclusions: Primary care individuals presented intermediate cardiovascular risk in the FRS and high risk in the WC, with no agreement between scores. Hypertension, diabetes, stress, obesity, and HDL-c represented the factors that were most associated with these scores.